Penerapan Akupresur dan Terapi Aroma Lavender pada Ibu Hamil Trimester Pertama untuk Mengurangi Morning Sickness Di Wilayah Kerja Puskesmas Limboto - Abunio, Indriyani; Retni, Ani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Nausea and vomiting in pregnant women are physiological, but if not treated immediately, the mother will experience hyperemesis gravidarum, so it requires non-pharmacological techniques to overcome the discomfort experienced by pregnant women. Objective: to apply acupressure and lavender aromatherapy to pregnant women in the 1st trimester to reduce morning sickness in the Limboto Community Health Center Working Area. Method: This research uses the experimental design method (two group pre-test post-test design), this type of research is carried out with how to divide two sample groups. The sample used in this research consisted of 14 respondents from first trimester pregnant women who experienced morning sickness who were divided into 2 groups. Result: Onadministering acupressureThe value obtained is sign.(2-tailed) pre = .000 ≤ 0.05 and the value obtained is sign. (2-tailed) post=.000 ≤ 0.05, while giving lavender aromatherapyThe value obtained is sign.(2-tailed) pre = .000 ≤ 0.05 and the value obtained is sign.(2-tailed) post = .000 ≤ 0.05. Conclusion: There is an effect before and after giving acupressure and giving lavender aromatherapy on reducing nausea and vomiting in pregnant women in the first trimester in the working area of the Limboto Community Health Center.Suggestion:Can be used as information and knowledge in improving and maintaining health status as well as applying research on administering acupressure and lavender aromatherapy to reduce nausea and vomiting